Defending Ukraine with EU weapons: arms control law in times of crisis. Issue 3 (September 2022) - Hamilton, Tomas
Abstract: The wish from 24 February 2022 onwards to help Ukraine defend against Russian aggression has led to the provision of unprecedented lethal European Union (EU) military assistance. As the 'taboo' of supplying lethal assistance into non-EU conflicts is swept aside, what is the role of international arms control law? The legal requirements of the EU Common Position on arms exports and the Arms Trade Treaty compel EU Member States to assess various short- and long-term risks associated with arms exports. But it is unclear how arms control norms are being taken into account by the EU Council in its rapidly evolving role as a peacemaker. The standards that are being used to shape EU decision-making on Ukraine matter both for their precedent-setting as reflecting the trajectory of EU normative power, as well as on the long-term blowbacks of proliferation on illicit arms trafficking. While from the EU Council, there has been limited public articulation of these risks, greater consideration thereof would serve as a reminder of the reality of post-conflict arms proliferation, ie. illicit arms trafficking of weapons leached from the conflict, and their subsequent misuse by undesirable actors. Geostrategic precedent is being set, with implications that extend far beyond Ukraine, including to other conflicts where the EU is already intervening. The EU's delivering of massive lethal military assistance alters also the reflexive perception of its institutions.